Women and cities. The conquest of urban space - Carrera, Letizia; Castellaneta, Marina (Frontiers in Sociology, 2023)
In the city of the Nineteenth-century, transformed by the values of the revolution and by the modernity, women did not have yet full citizenship. The public space was still strongly a male space and women, still with a weak public subjectivity, remained the object of the male gaze. Women have begun a process of conquering urban space by claiming their right to the city, through their physical presence in the city itself. Through physical space, women have claimed full symbolic citizenship. The project of an inclusive city takes shape from the public demands of women who, as Annie Hockshild wrote, gave birth to the most important revolution of the twentieth century. A stalled revolution, however, which still today requires a legislative protection for the project of the substantial equality, which is still not fully achieved. In addition to the various national legislations, international legislation also recognizes the central objective of guaranteeing women’s right to full citizenship. In the second part of the article, the focus is precisely on the normative content of this legislation and in particular on the objectives of the UN Agenda 2030.